Acyclic Nucleoside Phosphonates Bearing (R)‐ or (S)‐9‐[3‐Hydroxy‐2‐(phosphonoethoxy)propyl] (HPEP) Moiety as Monomers for the Synthesis of Modified Oligonucleotides. Issue 37 (7th August 2018) - Kaiser, Martin Maxmilian; Novák, Pavel; Rosenbergová, Šárka; Poštová‐Slavětínská, Lenka; Rosenberg, Ivan; Janeba, Zlatko
Abstract : Suitably protected ( R )‐ and ( S )‐HPEP 9‐[3‐hydroxy‐2‐(phosphonoethoxy)propyl] derivatives containing adenine and thymine nucleobases were prepared as monomers for the introduction of acyclic nucleotide units into oligonucleotides. The solid phase synthesis of a series of ribo and 2′‐deoxyribo nonamers containing ( R )‐HPEP and ( S )‐HPEP units was successfully performed in both 5′ → 3′ and 3′ → 5′ directions. The measurement of thermal characteristics of the complexes of modified nonamers with complementary DNA and RNA strands revealed a general destabilizing effect of the introduced acyclic units on the thermal stability, but in several cases [ modif. RNA*RNA and modif. DNA*RNA with ( S )‐HPEPA units], the duplexes were characterized in terms of T m values. Abstract : A solid‐phase synthesis afforded a series of ribo and 2′‐deoxyribo nonamers containing acyclic nucleotide units. A general destabilizing effect of the introduced acyclic units on the thermal stability of complexes of modified nonamers with the complementary DNA and RNA strands was observed, but in cases with ( S )‐HPEPA units, the duplexes were characterized in terms of T m values.